Answer:
The constant term in the function is 5
Explanation:
we have
![f(x)=x^(2)+8x+b](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5706c7c9bot0h6copbv38i4w8razx9nbr5.png)
where
b is the y-intercept or the constant term of the function
Remember that
The x-intercept is the value of x when the value of the function is equal to zero
so
For x=-3 ----> f(x)=0
For x=-5 ----> f(x)=0
substitute any of the intercepts in the function
For x=-3
![0=(-3)^(2)+8(-3)+b](https://img.qammunity.org/2021/formulas/mathematics/middle-school/oqct6wiff96g0ft0wng7rwmsuqwtxfl1lk.png)
![0=9-24+b](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1nd0klnmi1iaogx2sjhq0hga0hv9tmw66j.png)
![0=-15+b](https://img.qammunity.org/2021/formulas/mathematics/middle-school/m6479ytpxdcpe9ow06aq8hocghpb2ifqsr.png)
![b=15](https://img.qammunity.org/2021/formulas/mathematics/middle-school/eiwwne6mvj9ui2d9mo208gfuq9zce1yme3.png)
![f(x)=x^(2)+8x+15](https://img.qammunity.org/2021/formulas/mathematics/middle-school/g8zvjul6w3j70gpn2n9vbqi76tkkkinjnm.png)
Verify with the other intercept
For x=-5
![0=(-5)^(2)+8(-5)+15](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7w0mvhdnxzrip88qmldeqolq939ncrb247.png)
![0=25-40+15](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7d056xqmvhd3lnkinz0zripmwicv0frd2e.png)
---> is true
therefore
The constant term in the function is 5